PATHOLOGICAL STUDY OF PNUMONIA IN SHEEP AND GOAT IN ABTTOITR AT DUHOK PROVINCE - Balqes A. Ali; M. A. Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate histopathological changes in the lungs of sheep and goat. A total of 4061 lung samples (3667 sheep and 394 in lungs goats), All samples were collected during October 2020 till October 2021. According to macroscopical and histopathological features, different types of pneumonia with percentages rate in both of sheep and goat are recorded, which are including acute suppurative pneumonia, acute suppurative bronchopneumonia, Acute fibrinous pneumonia, acute fibrinous bronchopneumonia, interstitial pneumonia, Broncho-interstatial pneumonia, chronic granulomatous pneumonia, Haemoorgic pneumonia, acute and chronic bronchopneumonia, acute bronchitis and bronchiolitis, chronic bronchitis and bronchiolitis, Broncho-interstitial Pneumonia, verminous pneumonia and Embolic pneumonia. The results showed different macroscopical and histological features according to types of pneumonia and variation between both animals, pneumonia is an important disease in the lungs of small ruminant, and suppurative Pneumonia was the most predominant type while verminous pneumonia was detected only in few cases